(untitled) (East West Medical College Journal, 2026)
Polycystic ovary syndrome (PCOS) is a universally prevailing abnormal endocrinological disorder of reproductive-age women leading to subsequent anovulatory infertility. Initially, the Rotterdam criteria of laboratory reports, clinical presentation, and images support the diagnosis of polycystic ovary syndrome, although the ultrasound assessment was significantly limited. The approach of three-dimensional ultrasound proposes exact diagnoses and exceptional perception of PCOS pathophysiology. Meanwhile, Three-dimensional (3D) ultrasound improved the image and quality valuation of the volume of the ovarian, stromal, count of follicles, and blood flow inside the ovary. A systematic review performed under published literature concerning PCOS diagnosis determine by the gaudiness of three-D ultrasonography. Searching eligible English written literature with keywords of different terms of PCOS using 3-dimensional ultrasound. We review a total of eleven studies with 397 PCOS patients determined by 3-dimensional ultrasound that may reliable assessment report for a favor to PCOS. The standardized criteria method is preferred for each study’s quality assessment. The value of statistics determines by the report of compliance between three reviewers. However, regarding 3-dimensional ultrasound method is extensive for the advantage of practice, accuracy, predictability, and potentially promoted standard diagnosis of POCS along with Rotterdam criteria. EWMCJ Vol. 14, No. 1, January 2026: 71-77